Solubility behavior of pure components (camphene and caryophyllene oxide) at subcritical and supercritical conditions of carbon dioxide - Yeoh, Hooi Sim (2014)
Subcritical and supercritical fluids are good solvents because they possess liquid-like density and gas-like diffusivity and viscosity, which allow quick equilibration and micro pore permeation of fluid. Advantages of using subcritical and supercritical fluid are environmental friendly, less contamination of final product, energy saving and easy to control. In order to develop subcritical and supercritical processes, fundamental knowledge about thermophysical properties and phase equilibrium knowledge are crucial. With solubility data of compounds in subcritical and supercritical condition of solvent, these processes can be designed, scaled up and optimized. One major problem currently is that this fundamental knowledge is still lacking or limited to specific thermodynamic range. With all these problems, this study is significant with objectives to design and develop an experimental rig for solubility study, to investigate the effect of temperature and pressure on solubility behavior and to identify suitable mathematical model that correlates solubility data with changes of thermodynamic condition. In this study, solubility behavior of two active compounds from Malaysia local herbs, which are camphene and caryophyllene oxide, were investigated because of their medicinal values and unavailability of their solubility data. Experimental apparatus was developed based on dynamic method that coupled with off-line gravimetrically analysis for its convenience and better accuracy. As the apparatus had been assembled, it was subjected to validation with naphthalene to determine suitable flow rate for the experiment (4 ml/min) and to check the workability and accuracy of apparatus. Then, solubility study was carried out for camphene and caryophyllene oxide under subcritical (298. 15K and 303.] 5 K, 50 - 70 bar) and supercritical conditions (308. I5 K and 3 I 3.] 5 K for camphene, 308. 15K and 3 I 8. 15K for caryophyllene oxide; 80 _ 250 bar) of carbon dioxide. Solubility behavior of both compounds under subcritical carbon dioxide condition increased significantly with minor increment in pressure and temperature because density of solvent is very sensitive in subcritical region. In supercritical condition, retrogradation behavior happened and therefore solubility of both compounds decreased when temperature increased. However, solubility of both cornpound-; still increased with pressure. Three commonly used semi-empirical models. Which are Bartle model. Chrastil model. and Mendez-Santingo-Teja model, were tested to correlate solubility data with density of carbon dioxide. Of these three models, Mendez-Santiago-Teja model showed excellent fitting for both compounds in subcritical and supcrcritical condition with average absolute relative deviataion kept below 21%